Food safety in informal public markets in Kenya: perceptions of stakeholders in the food chain - Kuboka, Maureen; Grace, Delia; Artursson, K.; Lindahl, Johanna F.; Carlsson, G.; Mutua, Florence (Frontiers Media, 2024)
Introduction: Informal markets play a crucial role in providing fresh and nutritious foods for people in low and middle-income countries. However, the safety of food sold in these markets remains a major concern, contributing to a high burden of foodborne illnesses.